Hubungan Kadar Protein S100B Serum dengan Volume Perdarahan dan Tingkat Keparahan Pasien Perdarahan Intraserebral Spontan - Fadrian Herjunio; Syarif Indra; Restu Susanti; Yuliarni Syafrita; Dedi Sutia; Reno Bestari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Spontaneous intracerebral hemorrhage is a hemorrhagic stroke with high mortality and morbidity rates. Hemorrhage volume and the degree of neurological severity are important factors influencing prognosis. Brain tissue damage due to hemorrhage triggers the release of biomarkers such as S100B protein, which is secreted by astrocytes. This study aims to determine the relationship between serum S100B protein levels and the volume of bleeding and severity in patients with spontaneous intracerebral hemorrhage. This observational, analytical, cross-sectional study was conducted on 47 patients with primary spontaneous intracerebral hemorrhage aged ≥18 years with onset within 0–24 hours, admitted to Dr. M. Djamil Padang General Hospital between August 2025 and February 2026 and confirmed by head CT scan. Serum S100B protein levels were measured using an enzyme-linked immunosorbent assay (ELISA), hemorrhage volume was assessed using the Broderick method, and severity was assessed using the NIHSS score. Statistical analysis used the Mann-Whitney and Kruskal-Wallis tests. A total of 30 patients (63.8%) had a bleeding volume <30 cc and 27 patients (57.4%) had moderate neurological deficits. The median serum S100B protein level was 0.049 µg/L. There was a significant median difference between serum S100B protein levels and hemorrhage volume (p=0.047), but not with clinical severity based on the NIHSS (p=0.173). Serum S100B protein levels differed significantly between the small and large hemorrhage volume groups, but not across clinical severity groups based on the NIHSS.